The effect of service guarantee strength on service quality of online merchants. (2016) - Peng, Hong; Jiang, Wei; Su, Ruihuan
The authors attempted to study the relationship between service guarantees and service quality in network settings. Based on series of e-service quality evaluation models which were demonstrated in previous works, the authors considered the quality of e-services in four aspects including information quality, interaction quality, process quality and outcome quality. The moderator in above relationship is business reputation. Through analysing the secondary data collected from Taobao, a popular online shopping platform, the authors implied that service guarantee strength bring significantly positive impacts on information quality and interaction quality of online merchants. Moreover, compared with high level reputation, lower level reputation will strengthen the effect of service guarantees on interaction quality. Finally, some suggestions were put forward to improve service quality for online retailers to satisfied customers.